The Effect of Resistance Training With Electrical Muscle Stimulation on Atrogin-1 and Muscle Ring Finger-1 in Elite Male Athletes After Anterior Cruciate Ligament Surgery - Abouzar Alavi; Najmeh Rezaeian; Reza Ganji; Ali Yaghoubi (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims The cellular mechanisms preventing muscle atrophy after Anterior Cruciate Ligament (ACL) regeneration are not well understood. The aim of the present study was to evaluate the effect of resistance training combined with electrical muscle stimulation on serum levels of atrogin-1 and muscle RING finger-1 (MuRF1) in elite athletes following ACL surgery. Methods Among the elite athletes of Razavi Khorasan Province, 20 athletes voluntarily participated in the study and were divided into two groups (ten cases each), including 1) resistance training- electrical muscle stimulation (RT-EMS), and 2) resistance training (RT). The subjects in both groups performed 2-4 sets of resistance exercises (knee extension machine, squat, and knee flexion machines) at an intensity of 30-70% of ten repetitions for 12 weeks. The subjects in the RT-EMS group performed the exercises in combination with electrical stimulation at 35-70 Hz. Blood samples were collected from all subjects before and 48 hours after the last training session to measure atrogin-1 and MuRF1 levels. Analysis of covariance (ANCOVA) and paired t-test were used to compare between- and within-group changes, respectively, and a P<0.05 was considered significant. Results The results showed that 12 weeks of resistance training- electrical muscle stimulation significantly decreased serum levels of atrogin 1 (P=0.013) and MuRF1 (P=0.008) in the post-test compared to the pre-test. In addition, the between-groups comparison showed a significant difference in atrogin 1 levels between the RT-EMS and RT groups (P=0.047). Conclusion It can be suggested that resistance training in combination with electrical muscle stimulation is associated with lower levels of muscular atrophy proteins, such as atrogin-1 and MuRF1, and therefore, can be more effective than resistance training alone.